The effect of different degree of ripeness of tomato (Lycopersicon esculentum) on the quality of tomato sauce - Fullon, Lea S. (1997.)
Three ripening levels of tomatoes obtained from Miagao local market were processed into tomaro sauce.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Tomato; Ripeness; Tomato sauce